Job Creation in Latin America : Recent Trends and Policy Challenges - Pagés, Carmen; Pierre, Gaëlle; Scarpetta, Stefano (Washington, DC: World Bank and New York: Palgrave Macmillan, 2012)
This book strives to better understand the recent labor market trends in the countries of the region and the factors that underlie the failure of many of those countries to create more, but especially more productive and rewarding jobs. In particular, the book addresses four main questions: how well are the Latin American and Caribbean economies doing in terms of growth and job creation compared with other emerging economies? The book shows that jobless growth concerns only a few Latin American and Caribbean countries. In most of the rest, many jobs have been created over the past decade, but their productivity and pay were low. Is the weak creation of productive jobs the result of lack of dynamism in the economy? To address this question, the book dives into the behavior of firms. In particular, it looks at how resources are reallocated across firms and sectors. This analysis uncovers that, in most countries of the region, many jobs are created and destroyed, but this activity does not necessarily lead to better allocation of labor to the most productive jobs. Many new and potentially productive firms are small and encounter difficulties in expanding. What are the constraints to productive job creation across different types of firms? The book exploits information from a large number of firms in Latin America and the Caribbean regarding their exposure to and the effect of different aspects of the business climate in the region. Particular emphasis is placed on assessing differences across small, medium, and large firms and, when available, contrasting the responses of formal and informal firms. The book shows that small firms tend to be more constrained by lack of access to finance, macroeconomic instability, competition from informal firms, and corruption, while large firms are hampered by an inappropriate regulatory environment. What is the relative importance of labor market policies in strengthening the creation of productive jobs in the countries of the region? Firms in the region seldom cite labor market regulations as a major concern, even though those regulations are relatively rigid from an international perspective. The book shows that this apparent lack of concern is mainly because other constraints to firms' operation and expansion are more pressing. It also suggests that as other constraints are lifted, inappropriate labor market regulations become a binding constraint. The book goes on to advocate rethinking social protection systems, shifting protection from jobs to workers, and advancing the design of social security programs and labor market policies. The overarching goals are to protect workers while fostering the creation of more and better jobs.